The Reserpine Production and Callus Growth of Indian Snake Root (Rauvolfia serpentina (L.) Benth. Ex Kurz) Culture by Addition of Cu2+ - NUNUNG NURCAHYANI; SOLICHATUN SOLICHATUN; ENDANG ANGGARWULAN (Society for Indonesian Biodiversity, 2008)
The objectives of this research were to study the effects of Cu2+ addition on the reserpine production and callus growth from in vitro culture indian snake root (Rauvolfia serpentina (L.) Benth. Ex Kurz). This research frame work was based on the potency of snake root which was many exploited as anti-hypertension. The addition of elicitor Cu2+ in the form of CuCl2 would influence the ion transport of cell and changed of cytoplasm pH, and also has effects on synthesis and activity of enzymes which role in reserpine production and callus growth. The research was conducted in two steps, using Completely Randomized Design. The first step was the callus initiation to promote callus growth. Second step was the treatment to induce reserpine production. The callus was divided into five groups: 0; 5; 10; 20; 40; and 80 Î¼M. Morphology, wet weight, dry weight, growth rate, and reserpine content of callus were determined after 15 treatment day. Data were analyzed using ANOVA and continued by DMRT 5%. The result showed that reserpine production increased in addition of 5 Î¼M and 10 Î¼M Cu2+ in callus culture of R. serpentina and reduced in addition of Cu2+ more than 10 Î¼M. The callus growth significantly decreased by increasing concentration of Cu2+.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Rauvolfia serpentina, reserpine, elicitor, Cu2+, callus growth